PSIKOEDUKASI KEPADA CAREGIVER MENGENAI PERAN ENGAGEMENT DALAM TERAPI MUSIK PADA LANSIA DENGAN DEMENSIA - Prastyapadmaratri, Arumingtyas; Eudonia Raisa Blessinta Nadeak; Rafifah Anabela Putri; Clara R. P. Ajisuksmo (Jurnal Serina Abdimas, 2025)
Elderly individuals with dementia experience significant cognitive decline, which affects their quality of life. Music therapy, as a non-pharmacological intervention, has been proven effective in enhancing cognitive and emotional functions in elderly. This study aims to provide psychoeducation to caregivers regarding the role of engagement in music therapy for elderly individuals with dementia. The method employed involves delivering material through e-posters on the social media platform Instagram, designed to attract attention and increase audience interaction. The results indicate that this psychoeducation successfully garnered interest from many Instagram users, with a total of 288 interactions comprising likes, comments, saves, and shares. Positive feedback from the audience suggests that the content presented was informative and beneficial. The conclusion of this study is that psychoeducation via social media, especially Instagram, can enhance caregivers’ awareness of the importance of emotional, cognitive, and social engagement in music therapy, thereby assisting the elderly in accessing memories and managing their emotional and cognitive conditions. ABSTRAK Lansia dengan demensia mengalami penurunan fungsi kognitif yang signifikan, yang mempengaruhi kualitas hidup mereka. Terapi musik sebagai intervensi non-farmakologi terbukti efektif dalam meningkatkan fungsi kognitif dan emosional lansia. Penelitian ini bertujuan untuk memberikan psikoedukasi kepada caregiver mengenai peran engagement dalam terapi musik untuk lansia dengan demensia. Metode yang digunakan adalah penyampaian materi dengan e-poster yang diunggah melalui media sosial Instagram, yang dirancang untuk menarik perhatian dan meningkatkan interaksi audiens. Hasil menunjukkan bahwa psikoedukasi ini berhasil menarik minat banyak pengguna Instagram, dengan total 288 interaksi yang terdiri dari likes, komentar, saved, dan shared. Komentar positif dari para audiens menunjukkan bahwa konten yang disampaikan informatif dan bermanfaat. Dari penelitian ini, dapat ditarik kesimpulan bahwa psikoedukasi melalui media sosial Instagram dapat meningkatkan kesadaran caregiver tentang pentingnya keterlibatan emosional, kognitif, dan sosial dalam terapi musik, sehingga dapat membantu lansia mengakses kembali memori dan mengelola kondisi emosional dan kognitif mereka.